2016
DOI: 10.1038/leu.2016.238
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of the putative ubiquitin-E3 ligase PDLIM2 in classical Hodgkin and anaplastic large cell lymphoma

Abstract: Apart from its unique histopathological appearance with rare tumor cells embedded in an inflammatory background of bystander cells, classical Hodgkin lymphoma (cHL) is characterized by an unusual activation of a broad range of signaling pathways involved in cellular activation. This includes constitutive high-level activity of nuclear factor-κB (NF-κB), Janus kinase/signal transducer and activator of transcription (JAK/STAT), activator protein-1 (AP-1) and interferon regulatory factor (IRF) transcription facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 52 publications
(119 reference statements)
0
12
0
Order By: Relevance
“…Some previous studies reported that PDLIM2 expression was also regulated by the promoter methylation that blocks its transcription in colon cancer, 26 ovarian cancer 28 and classical Hodgkin and anaplastic large cell lymphoma. 29 However, whether its expression is related to the methylation status of its promoter in ESCC is still not clear.…”
Section: In Silico Analysis Of the Potential Genetic And Epigenetic Alterations Associated With Pdlim2 Dysregulationmentioning
confidence: 99%
“…Some previous studies reported that PDLIM2 expression was also regulated by the promoter methylation that blocks its transcription in colon cancer, 26 ovarian cancer 28 and classical Hodgkin and anaplastic large cell lymphoma. 29 However, whether its expression is related to the methylation status of its promoter in ESCC is still not clear.…”
Section: In Silico Analysis Of the Potential Genetic And Epigenetic Alterations Associated With Pdlim2 Dysregulationmentioning
confidence: 99%
“…Pdlim2 encodes an E3 ubiquitin ligase and ubiquitinates STAT3 and STAT4 to lead to their degradation [55,56]. Pdlim2 is reported to be associated with tumor suppression [57][58][59] and tumorigenesis [60, 61], but its function in the nervous system remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The PDLIM2 gene is repressed in different cancers, which implies its tumor suppressive role. Repression and a tumor suppressive role of PDLIM2 were observed in ATL induced by HTLV1 virus [2629], Kaposi sarcoma [30], ovarian cancer [31], gastric cancer [32], colon cancer [12], Hodgkin lymphoma [33] and breast cancer [34, 35]. In contrast to the above studies, a pro-oncogenic role and enhanced expression of PDLIM2 were observed in castration-resistant prostate cancer cells [5, 9, 36], invasive breast cancer cell lines and breast carcinomas [9, 11].…”
Section: Discussionmentioning
confidence: 99%